High resolution biosensor to test the capping level and integrity of mRNAs - Moya-Ramirez,I; Bouton,C; Kontoravdi,C; Polizzi,K (Nucleic Acids Research, 2020)
5 Cap structures are ubiquitous on eukaryotic mRNAs, essential for post-transcriptional processing,translation initiation and stability. Here we describea biosensor designed to detect the presence of capstructures on mRNAs that is also sensitive to mRNAdegradation, so uncapped or degraded mRNAs canbe detected in a single step. The biosensor is basedon a chimeric protein that combines the recognitionand transduction roles in a single molecule. The mainfeature of this sensor is its simplicity, enabling semiquantitative analyses of capping levels with minimalinstrumentation. The biosensor was demonstratedto detect the capping level on several in vitro transcribed mRNAs. Its sensitivity and dynamic rangeremained constant with RNAs ranging in size from250 nt to approximately 2700 nt and the biosensorwas able to detect variations in the capping level inincrements of at least 20%, with a limit of detection of2.4 pmol. Remarkably, it also can be applied to morecomplex analytes, such mRNA vaccines and mRNAstranscribed in vivo. This biosensor is an innovativeexample of a technology able to detect analyticallychallenging structures such as mRNA caps. It couldfind application in a variety of scenarios, from qualityanalysis of mRNA-based products such as vaccinesto optimization of in vitro capping reactions.